Human Stress Recovery during Exposure to Geranium Visual Stimuli - Kim, Eunhee; Mattson, Richard H (HortScience, 1998)
Evaluating human psychophysiological responses to plant visual stimuli provides a clearer understanding of factors within plant environments that enhance or maximize recovery from stress. Advances in physiological monitoring technology allow continuous recording and more-refined data collection of human responses to environmental stimuli. The objective of this study was to compare effects on stress recovery by exposures to geranium visual stimuli following an induced stressor, by measuring changes in physiological indicators and emotional states. One-hundred-fifty college students were randomly assigned to one of three treatment groups: red-flowering geraniums, non-flowering geraniums, or no geraniums. Each student viewed a 10-min film of a stressful human situation following a 5-min baseline, then was exposed to an assigned treatment setting during a 5-min recovery period. Continuous physiological measurements were taken of brainwave activities (EEG), skin conductance (EDR), and finger skin temperature. Self-rating scores of subjects' feelings were taken using the Zuckerman Inventory of Personal Reactions. Comparisons among treatment groups will be discussed based on gender and other demographic factors.